Increased SBPase activity improves photosynthesis and grain yield in wheat grown in greenhouse conditions. (26th September 2017) - Driever, Steven M.; Simkin, Andrew J.; Alotaibi, Saqer; Fisk, Stuart J.; Madgwick, Pippa J.; Sparks, Caroline A.; Jones, Huw D.; Lawson, Tracy; Parry, Martin A. J.; Raines, Christine A.
Abstract : To meet the growing demand for food, substantial improvements in yields are needed. This is particularly the case for wheat, where global yield has stagnated in recent years. Increasing photosynthesis has been identified as a primary target to achieve yield improvements. To increase leaf photosynthesis in wheat, the level of the Calvin–Benson cycle enzyme sedoheptulose-1, 7-biphosphatase (SBPase) has been increased through transformation and expression of a Brachypodium distachyon SBPase gene construct. Transgenic lines with increased SBPase protein levels and activity were grown under greenhouse conditions and showed enhanced leaf photosynthesis and increased total biomass and dry seed yield. This showed the potential of improving yield potential by increasing leaf photosynthesis in a crop species such as wheat. The results are discussed with regard to future strategies for further improvement of photosynthesis in wheat. This article is part of the themed issue 'Enhancing photosynthesis in crop plants: targets for improvement'.